Behavior of heat damaged circular reinforced concrete columns repaired using Carbon Fiber Reinforced Polymer rope. (September 2020) - Obaidat, Ala' Taleb; Ashteyat, Ahmed M.; Hanandeh, Shadi; Al-Btoush, Aseel Yousef
Abstract: This study aims to investigate the behavior of repaired circular reinforced concrete (RC) columns exposed to temperature considering the effect of spacing between CFRP ropes, area of CFRP ropes and degree of temperature. Nine circular column specimens with diameter of 185 mm and length of 800 mm were constructed and tested. The experimental RC column specimens were divided into three groups. The first group consisted of three circular RC columns not exposed to temperature, the second group consisted of three circular RC columns exposed to 400 °C and the third group consisted of three circular RC columns exposed to 600 °C. In each group, the first column was not repaired and used as control specimen, while the second and third RC column specimens were repaired with one layer of CFRP ropes at spacing of 100 mm and two layers of CFRP ropes at spacing of 200 mm, respectively. Results showed that the repaired circular RC columns damaged by heat up to 400 °C for 3 h with one layer of 100 mm spacing and two layers of 200 mm spacing exhibited load capacity of about 40% and 23%, respectively, of the load capacity of the control specimen. On the other hand, the load capacity of rehabilitated short circular RC columns damaged by heat up to 600 °C for 3 h with one layer of 100 mm spacing and two layers of 200 mm spacing were 88% and 64%, respectively, compared to the control specimen. CFRP effectiveness increases when decreasing the spacing between the CFRP ropes, which leads to a better effective lateral confining pressure. Complementary to the experimental work, a validated numerical finite element model was employed to investigate the effect of different parameters used in the experimental investigation on the stress-strain behavior of RC circular columns. Results of the numerical model showed good agreement with the experimental results. Highlights: Reinforced concrete columns exposed to heat of 400 °C and 600 °C for 3 h. Reinforced concrete column specimens were repaired with CFRP ropes. Regained load in columns exposed to high heat was more than ones exposed to low heat as control specimen. The effectiveness of CFRP increases when decreasing the spacing between the CFRP ropes. A validated numerical finite element model employed to investigate the effect of different parameters.